Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Disiplin Kerja Pegawai Bidang Keperawatan Pada Rumah Sakit Islam Surakarta - Indrawan, Daeng Muhammad Rum; , Drs. Farid Wajdi, MM, Ph.D (2016)
The aim of this research are to analyze the effect of work motivation for work discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS), to analyze the effect of work environment for work discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS), to analyze the effect of work motivation and work environment for work discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS). The data collection technique in this research used questionnaire method. The sample in this research are 77 employees in nursing of Surakarta Islamic Hospital (RSIS). The analysis tool those are used in this research are instrument test, classic assumption test, data analysis (multiple linear regression analyze, t-test, ftest, and determination coefficient (R2)). The result of this research are there is a significant effect between work motivation with work discipline discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS), there is a significant effect between work environment with work discipline discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS), together there is a significant effect between work motivation and work environment with work discipline discipline of the employees in nursing on Surakarta Islamic Hospital (RSIS).